2006
DOI: 10.1074/jbc.m507964200
|View full text |Cite
|
Sign up to set email alerts
|

The Unique NH2-terminally Deleted (ΔN) Residues, the PXXP Motif, and the PPXY Motif Are Required for the Transcriptional Activity of the ΔN Variant of p63

Abstract: p63, a member of the p53 family of transcription factors, is known to be involved in epithelial development. However, its role in tumorigenesis is unclear. Contributing to this uncertainty, the TP63 locus can express multiple gene products from two different promoters. Utilization of the upstream promoter results in expression of the TAp63 variant with an activation domain similar to p53. In contrast, the NH 2 -terminally deleted (⌬N) p63 variant, transcribed from a cryptic promoter in intron 3, lacks such an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 37 publications
5
94
0
Order By: Relevance
“…The accepted activity was its dominant negative effect exerted towards the TAp63 isoform, as suggested by co-transfection experiments in luciferase reporter assays [3]. However, in addition to the competition between TAp63 and Np63 isoforms, growing evidence indicated that these N-terminal isoforms had different transcriptional specificities a specificity confirmed by functional domain characterization [32][33][34], and microarray analysis showing that both isoforms can induce gene transcription [35,29]. As expected from genes important for developmental and differentiation processes, the more strongly represented classes of target genes are those concerned with cell adhesion, the cytoskeleton, and the cell cycle.…”
Section: Transcriptional Activities Of P63 Isoformsmentioning
confidence: 96%
“…The accepted activity was its dominant negative effect exerted towards the TAp63 isoform, as suggested by co-transfection experiments in luciferase reporter assays [3]. However, in addition to the competition between TAp63 and Np63 isoforms, growing evidence indicated that these N-terminal isoforms had different transcriptional specificities a specificity confirmed by functional domain characterization [32][33][34], and microarray analysis showing that both isoforms can induce gene transcription [35,29]. As expected from genes important for developmental and differentiation processes, the more strongly represented classes of target genes are those concerned with cell adhesion, the cytoskeleton, and the cell cycle.…”
Section: Transcriptional Activities Of P63 Isoformsmentioning
confidence: 96%
“…The DN isoforms can block the TA activity of the full-length proteins by forming complexes or by competing for DNA-binding sites (Grob et al, 2001;Stiewe et al, 2002;Chan et al, 2004). Several studies have also shown that DNp63 can activate transcription through an additional N-terminal TA domain (Ghioni et al, 2002;Helton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…138 However, this general assumption requires some caution since for instance, DNp63 isoforms are transcriptionally proficient. 139,140 All p53-family transcripts are also subject to alternative splicing at the C-terminus, independent of the promoter used, thus generating a combinatorial variety of isoforms (obtainable adjoining each N-terminal variant with any of the C-terminal variants). The longest C-terminal variant is dubbed a in p63 and p73, and comprises the SAM domain.…”
Section: Tap73 α αmentioning
confidence: 99%